2010
DOI: 10.2174/092986710791331059
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Membrane-Targeted Antibiotics

Abstract: Antimicrobial resistance continues to evolve and presents serious challenges in the therapy of both nosocomial and community-acquired infections. The rise of resistant strains like methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Staphylococcus aureus (VRSA) and vancomycin-resistant enterococci (VRE) suggests that antimicrobial resistance is an inevitable evolutionary response to antimicrobial use. This highlights the tremendous need for antibiotics against new bacterial targets. Agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 0 publications
0
29
0
Order By: Relevance
“…That is, this compound is applicable for raw and cold foods, as well as food products treated with high temperature, short time pasteurization. Bacterial membrane integrity is important not only for bacteria's self-protection but also for the functions of membrane-associated enzymes responsible for energy generation, respiration, and redox balance [24,25]. Thus, bacterial membrane rupture easily impairs these critical functions, which in turn affects the bacteria's survival and growth.…”
Section: Discussionmentioning
confidence: 99%
“…That is, this compound is applicable for raw and cold foods, as well as food products treated with high temperature, short time pasteurization. Bacterial membrane integrity is important not only for bacteria's self-protection but also for the functions of membrane-associated enzymes responsible for energy generation, respiration, and redox balance [24,25]. Thus, bacterial membrane rupture easily impairs these critical functions, which in turn affects the bacteria's survival and growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some reviews (Vooturi and Firestine 2010;Giuliani and Rinaldi 2011) have reported the engineering of AMP mimetics or peptidomimetics, ie non-peptide molecules aimed at retaining and improving the basic features of AMPs.…”
Section: Sources Of Antimicrobial Peptidesmentioning
confidence: 99%
“…LPS and (lipoteichoic acid) LTA binding activity (Giuliani and Rinaldi 2011) DL-Amino acid diastereomers . Do not retain a-helical structure of AMPs (Vooturi and Firestine 2010) . .…”
Section: Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts are being made to develop antimicrobial peptides with bactericidal properties to kill both gram-positive and gram-negative organisms, and this topic is discussed in the chapter by Gorr [pp. [84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Such agents have shown activity against clinically important multi-resistant bacteria, such as vancomycin-resistant enterococci and methicillin-resistant Staphylococcus aureus [98].…”
Section: Are Further Advances Possible?mentioning
confidence: 99%